IMPLEMENTASI MODEL TEAMS GAMES TOURNAMENT TERINTEGRASI KEARIFAN LOKAL MADURA DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV - Rifa'i, Moch; Silvia Ratna Dewi Diputri; Mohammad Edy Nurtamam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve students' learning motivation in mathematics through the application of the Teams Games Tournament (TGT) model integrated with Madura's local wisdom. The problem identified is the low motivation and active participation of students in learning mathematics in the fourth grade of elementary school. Based on the results of interviews with teachers and initial observations, students show a lack of enthusiasm in participating in math lessons and tend to be passive in class activities. To address this issue, the researcher used the TGT model based on teamwork and games that are engaging for the students. Additionally, the integration of local Madurese culture, particularly cow racing, is used to provide a context that is closer to the students' lives and make learning more relevant. This study uses the Classroom Action Research (CAR) method with two cycles consisting of the stages of planning, implementation, observation, and reflection. Data were collected through observations of student activities, interviews with teachers, and analysis of student learning documentation. The research results show that the implementation of the TGT model combined with the local Madura culture successfully significantly increased students' learning motivation, transforming the learning atmosphere into a more active and enjoyable one. This is evident from the increased participation of students in group activities and individual tasks, as well as the heightened enthusiasm of students in following mathematics lessons. This study concludes that the integration of local wisdom and a team-based learning approach can be an effective solution to enhance students' learning motivation.